Perbandingan Weight Moving Average dan Single Exponential Smoothing pada Peramalan Persediaan Produk Farmasi - Novita Sari; Hasdiana Hasdiana; Eka Rahayu (JITEKH, 2022)
Satria Pharmacy is a drug product selling business that only sells various kinds of pharmaceutical products. Pharmacies Satria often have difficulty in predicting future product inventories based on previously recorded data. Forecasting is very influential on the decision of the pharmacy owner to determine the number of pharmaceutical products that must be provided by the pharmacy. In developing this forecasting system, the writer uses the Weighted Moving Average (WMA) and Single Exponential Smoothing (SES) forecasting methods. The purpose of this study is to apply the Weight Moving Everage (WMA) and Single Exponential Smoothing (SES) methods to determine the accuracy of the Weight Moving Average (WMA) and Single Exponential Smoothing (SES) methods with the MSE technique. The results of this study are a website-based system that can forecast and produce value comparisons between the Weight Moving Everage and Single Exponential Smoothing methods where in the overall calculation of the error value with Mean Square Error (MSE) there are 54,95 for the WMA method and for the WMA method. SES has a value of 40,79, with that the SES method as a whole predicts better than the WMA method